PRESERVATION OF TRADITIONAL BALINESE DANCE IN MEKAR SARI VILLAGE, BANGGAI REGENCY, CENTRAL SULAWESI PROVINCE - Lestari, Ni Made Widi; Apriyanto, Joni; Arrazaq, Naufal Raffi; Tasnur, Irvan (CV. Fahr Publishing, 2025)
The preservation of local culture has become an urgent issue amid the rapid pace of globalization. This challenge is particularly significant in transmigration areas, where people from diverse ethnic backgrounds interact and coexist. Mekar Sari Village, located in Banggai Regency, Central Sulawesi Province, serves as an interesting case study. This village illustrates how the Balinese transmigrant community strives to maintain their cultural identity within a socially diverse and multicultural environment. Although geographically distant from their ancestral homeland in Bali, the people of Mekar Sari Village demonstrate remarkable spirit and commitment. They are highly dedicated to preserving their ancestral cultural heritage, especially through traditional dance. This study specifically focuses on exploring the various forms and strategies employed by the local community in Mekar Sari to sustain Balinese traditional dance. A qualitative approach with a descriptive method was used to collect data, involving direct field observation and in-depth interviews with cultural practitioners. The findings emphasize that cultural preservation is carried out across generations. Furthermore, Hindu religious ceremonies function as a medium to uphold cultural values, both spiritually and symbolically. Despite facing various challenges, the community remains consistent and steadfast in safeguarding their cultural identity. The study concludes that active participation of the local community is a key and determining factor in the sustainability of traditional culture in transmigration areas such as Mekar Sari Village. Without their involvement, cultural preservation would be extremely difficult to achieve.